(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Emotion" is referred to as "rasa," while "state of mind" is referred to as "bhava." Kathak is a kind of traditional Indian dance that is renowned for the expressive movements and facial emotions that are included in the performance. There hasn’t been a lot of studies done on the facial expressions that Kathak dancers use. Deep learning is a strong technique that may be used for the task of analyzing and classifying the facial expressions of Kathak dancers. In order to find an answer to this research issue, a dataset consisting of the facial expressions shown by Kathak dancers will be compiled and then subjected to deep learning algorithms for analysis. The findings of this research will help us get a better knowledge of the facial expressions used by Kathak dancers as well as the feelings that are communicated via this style of dance. Kathak face expressions are nine types namely- Adbhut(wonder), Hasya(joy), Shringar(affection), Bheebatsya(loathing), Bhayanak(terror), Roudra(anger), Veer(pride), Karuna(sadness) and Shant(peace). These expressions are mapped to Kathak dancers’ expressions for better classification through face detection and extraction. Image preprocessing and classification are performed to achieve maximum accuracy. Using Convolutional Neural Network(CNN). The scope of the paper is to identify the facial expressions of Kathak dancers to have a better understanding of the art in the teaching and learning paradigm.